Odpowiedzi

2010-03-01T00:16:45+01:00
1.
∫▒(x-3)/(x^2-6x+3) dx =
t = x^2-6x+3 dt=(2x-6)dx 1/2dt =(x-3)dx
∫▒dt/2t = 1/2 ln t = 1/2 ln (x^2-6x+3)

2.
∫▒ln⁡(x)dx =

u = ln(x) v' = 1
u'=1/x v=x
xln(x) - ∫▒dx = xln(x) -x

3.
∫▒√((x-1)/(x+2)) dx/〖(x-1)〗^2 =
(x+2)/(x-1)=t dt=1/(x-1)^2dt
∫▒1√t dt = 2√t = 2√(x+2)/(x-1)

4.
∫▒dx/(e^2x-1)
e^2x-1=t 2e^2x dx = dt
dx=dt/2e^2x
e^2x = t+1
dx = dt /2(t+1)

∫▒dt/2t(t+1)dt = 1/2∫▒((1/t)-(1/t+1))dt = 1/2 ln(t) - 1/2 ln(t+1) =
1/2 ln(e^2x-1) - 1/2 ln(e^2x) =1/2 ln(e^2x-1) - x



5.
∫▒ln⁡(x^2+1)dx
u = ln(x^2+1) v' = 1
u'=2x/x^2+1 v=x
xln(x) - ∫▒2x^2 dx/x^2+1 = xln(x) - 2∫▒(x^2+1-1) dx/x^2+1
xln(x) - 2∫▒dx + 2 ∫▒dx /x^2+1 = xln(x) - 2x + arc tg(x)

6.
∫▒1/((3-2x)) dx

3-2x = t dt = -2dx dx= -1/2 dt
∫▒-1/2t dt = -1/2 ln (t) = -1/2 ln(3-2x)


2010-03-01T02:35:14+01:00
Obliczyć całki
∫▒(x-3)/(x^2-6x+3) dx=1/2∫▒dt/t=1/2 lnItI=1/2 lnIx^2-6x+3I +C, C∈R
przez podstawienie
x^2-6x+3=t
2x-6 dx=dt /:2
x-3 dx=1/2dt

∫▒ln⁡(x)dx =
przez części ze wzoru:∫▒ u*v'=u*v-∫▒ u'*v
u=ln⁡(x)
u'=1/x
v'=1
v=x
∫▒ln⁡(x)dx =x*ln⁡(x)I-∫▒ 1/x*x dx=x*ln⁡(x)I-∫▒ 1 dx=x*ln⁡(x)I- x +C, C∈R


∫▒√((x-1)/(x+2)) dx/〖(x-1)〗^2 =∫▒ √1/t dt=∫▒ t ^(-1/2)dt=2 t ^1/2=2 √t=
2 √[(x+2)/(x-1)] +C, C∈R

przez podstawianie:
trzeba zauważyć, że ((x+2)/(x-1)) ' = 1/(x-1)²
(x+2)/(x-1)=t
1/(x-1)² dx=dt


∫▒dx/(e^2x-1)=∫▒ 1/2 *1/(t+1) *1/t dt=1/2∫▒ 1/(t+1)*t dt
przez podstawianie:
e^2x-1=t
2e^2x dx=dt
dx=1/2 e^(-2x)dt
dx=1/2 *1/(t+1)dt

teraz trzeba rozłożyć na ułamki proste:
1/(t+1)*t= A/t+1 + B/t
1/(t+1)*t= At/(t+1)t + B(t+1)/t(t+1)
1/(t+1)*t= At + B(t+1)/t(t+1)
A+B=0
B=1
A=-1
1/(t+1)*t= -1/t+1 + 1/t
czyli całka=1/2∫▒ -1/t+1 dt +1/2∫▒ 1/t dt = -1/2ln It+1I +1/2 lnItI=
-1/2ln Ie^2x-1+1I +1/2 lnIe^2x-1I=
-1/2ln Ie^2xI +1/2 lnIe^2x-1I=
-1/2*2x +1/2 lnIe^2x-1I=-x +1/2 lnIe^2x-1I+C, C∈R


∫▒ln⁡(x^2+1)dx =x*ln⁡(x^2+1)I - ∫▒ 1/(x^2+1) *2x *x dx=
x*ln⁡(x^2+1)I - ∫▒ 2x²/(x^2+1)dx=x*ln⁡(x^2+1)I - ∫▒ 2x²+2-2/(x^2+1)dx=
x*ln⁡(x^2+1)I - 2∫▒ 1dx+ 2∫▒ 1/(x^2+1)dx=
x*ln⁡(x^2+1)I - 2x + 2arc tg ((x^2+1)) +C, C∈R

przez części:
u=ln⁡(x^2+1)I
u'=1/(x^2+1) *2x
v'=1
v=x


∫▒1/((3-2x)) dx = -1/2 ∫▒ 1/t dt=-1/2 lnItI=-1/2 lnI3-2xI +C, C∈R
podstawienie:
3-2x=t
-2 dx=dt /:(-2)
dx=-1/2 dt